Development of the Concept Design of Rooftop Solar Power Plant Practice Tool - Stieven Netanel Rumokoy; I Gede Para Atmaja; Maureen Langie; Josephin Sundah (Universitas Raharja, 2022)
Solar energy source as an alternative to gain electrical energy continues to grow. One of the utilization systems is to use the solar panels on the roof top of the house. The Household-scale of Solar System Power Plant has been widely used. This case requires skilled workers for the installation of this system. This study aims to develop a household-scale of Solar System Power Plant practice tool into a complete system. The used method begins with a literature study and then continues with the design system. The results obtained are a household-scale Solar System Power Plant tool design that can describe a complete system of the electrical energy distribution. The concept of a practical tool that previously only focused on the mechanical installation of solar panels but now become more complete with the addition of an electrical energy distribution system.